Arene-ruthenium complexes with ferrocene-derived ligands: Synthesis and characterization of complexes of the type [Ru(?6-arene)(NC5H4CH2NHOC-C5H4FeC5H5)Cl2] and [Ru(?6-arene)(NC3H3N(CH2)2O2C-C5H4FeC5H5)Cl2] - Auzias, Mathieu; Gueniat, Joel; Therrien, Bruno; Süss-Fink, Georg; Renfrew, Anna K.; Dyson, Paul J. (My University, 2009)
Pyridylferrocene and imidazolylferrocene arene-Ru complexes [Ru(?6-arene)(L)Cl2] where L = NC5H4CH2NHOCC5H4FeC5H5, arene = p-iPrC6H4Me (1) or C6Me6 (2); L = NC3H3N(CH2)2O2CC5H4FeC5H5, arene = p-iPrC6H4Me (3) or C6Me6 (4), and diruthenium-arene complexes [Ru(?6-arene)Cl2]2(L) where L = 1,1'-(NC5H4CH2NHOC)2C5H4FeC5H4, arene = p-iPrC6H4Me (5) or C6Me6 (6); L = 1,1'-(NC3H3N(CH2)2O2C)2C5H4FeC5H4, arene = p-iPrC6H4Me (7) or C6Me6 (8) were synthesized and characterized. The mol. structures of 1 and 3 were confirmed by single-crystal x-ray diffraction. The in vitro anticancer activities of complexes 1-8 were studied comparatively to the uncoordinated ligands. The complexes exhibit fairly low cytotoxicities in comparison to related ferrocene-derived arene-Ru complexes. [on SciFinder(R)]
Keywords: arenedichlororuthenium dimer reaction pyridylferrocene imidazolylferrocene; ferrocenecarboxylic acid chloride reaction picolylamine hydroxyethylimidazole arenedichlororuthenium dimer; crystal structure areneruthenium pyridylferrocene imidazolylferrocene prepn carcinostatic ovarian carcinoma; mol structure areneruthenium pyridylferrocene imidazolylferrocene prepn carcinostatic ovarian carcinoma